2015
DOI: 10.1103/physreve.91.032145
|View full text |Cite
|
Sign up to set email alerts
|

Phase transitions in a frustrated Ising antiferromagnet on a square lattice

Abstract: The phase transitions occurring in the frustrated Ising square antiferromagnet with first- (J1<0) and second-nearest-neighbor (J2<0) interactions are studied within the framework of the effective-field theory with correlations based on the different cluster sizes and for a wide range of R=J2/|J1|. Despite the simplicity of the model, it has proved difficult to precisely determine the order of the phase transitions. In contrast to the previous effective-field study, we have found a first-order transition line i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 28 publications
3
22
0
Order By: Relevance
“…It is worth to stress that the nature of the phase transitions in this model is a topic of current debate. For instance, an effective field-theory study using clusters of up to 9 sites indicated the presence of a discontinuous phase transition between PM and AF states [23]. However, our results indicating only continuous phase transitions for the PM/AF phase boundary are in agreement with Monte Carlo simulations [10] and cluster variation method calculations [9].…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…It is worth to stress that the nature of the phase transitions in this model is a topic of current debate. For instance, an effective field-theory study using clusters of up to 9 sites indicated the presence of a discontinuous phase transition between PM and AF states [23]. However, our results indicating only continuous phase transitions for the PM/AF phase boundary are in agreement with Monte Carlo simulations [10] and cluster variation method calculations [9].…”
Section: Resultssupporting
confidence: 85%
“…In particular, our approach indicates that tricriticality occurs at g * = 0.66 [5,6], which is much closer to the Monte Carlo simulations (g * MC ≈ 0.67) [12,13] than the effective field theory predictions (g * EFT = 0.97) for the largest cluster considered in Ref. [23]. It reinforces that the present approach incorporates important geometrical features of the model, providing an appropriate starting point to study the role of transverse field.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…Since only an approximate expression exists for the free energy at finite temperature in the frame of the EFT based on any spin cluster (see, e.g. [12,19]), we have confined our calculations only to the second-order phase transitions, including the TCP.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, the MCS predicts that FCO phase does not exist at any T > 0 [34]. Moreover, forμ = 0 and the SQ lattice the first-order CBO-SCO transition is not present at T > 0 and these two phases are separated by the NO phase region [34,40,41]. The situation changes in three dimensions for simple cubic lattice, where that transition occurs [42].…”
Section: Conclusion and Final Remarksmentioning
confidence: 92%